The Relationship Between Malnutrition And Malocclusion: Literature Review: English - Wahyuni Dyah Parmasari (Sriwijaya Journal of Dentistry, 2024)
Introduction: Nutrition is a crucial factor in the body's growth and development process, particularly for the jawbones and teeth. A lack of proper nutrition can lead to slow growth of the maxilla and mandible, resulting in an imbalance in the relationship between the upper and lower jaw arches. This disharmony can cause malocclusion. The objective of this study was to review the most recent cross-sectional studies from the last 10 years that report on the relationship between malnutrition and malocclusion. Purpose: To find out more information on the influence of malnutrition on the occurrence in malocclusion. Methods: The literature survey was carried out using the Google Scholar, Sciencedirect and PubMed databases. Data search utilized the Boolean Search method. Results: The initial search yielded 58 citations which were then selected and duplicates were removed. There were 10 articles found. Conclusion: The studies cited in this literature review indicate that not all journals suggest a significant difference between malnutrition and malocclusion.